Case report: New subtype of gastric adenocarcinoma arising from an H. pylori infection-negative stomach: Foveolar epithelium and mucous neck cell-mixed type adenocarcinoma - Liu, Xuemei; Wu, Xinglong; Zhu, Jiaxing; Yagi, Kazuyoshi; Ajioka, Yoichi; Terai, Shuji; Mizuno, Kenichi; Li, Hongping; Tuo, Biguang; Di, Lianjun (Frontiers in Oncology, 2022)
The characteristics of Helicobacter pylori (H. pylori) infection-negative gastric cancer have not been well documented because of its rarity, despite several types of H. pylori infection-negative gastric cancers being reported. In this report, we describe a case of early gastric cancer that developed without H. pylori infection with characteristic magnifying narrow-band imaging and novel histological findings. The difficulty in making an accurate diagnosis and differential diagnosis is highlighted, with the goal of providing more clinical experience for the diagnosis of H. pylori infection-negative gastric cancer.